Pengembangan Kapasitas Guru dalam Meningkatkan Kesejahteraan di SD Inpres 45 Ambon - Lisye Magdalena Liur; Teddy Christianto Leasiswal; Wiljan Atfentia Kotngoran; Altje Delaya Tamole (Yayasan Literasi Sains Indonesia, 2025)
The purpose of this community service activity is to enhance the capacity of teachers at SD Inpres 45 Ambon thru a workshop with the theme